Profitabilitas Strategi Momentum di Bursa Efek Indonesia (Periode Januari 2003 – Desember 2007) - B Yuliarto Nugroho (Jurnal Siasat Bisnis, 2008)
Momentum trading strategy present challenges to the concept of efficient market theory. Many studies investigate the profitability of momentum trading strategy in international and domestic equity market and evidence has shown that this strategy could lead to abnormal profit. The purpose of this paper are to examine and analyse the profitability of momentum strategy in the Indonesia equity market from January 2003 to December 2007. This paper also investigates factor such as size and trading volume to identify potential source of profits in momentum strategy. The result of this research show that short-term momentum strategy are profitable on all stock listed on IDX. The findings of the research also show that in the shortterm, trading volume have significant effects and could be potential source of profits in momentum strategy.Keywords: profitability, momentum, size, trading volume